Battery, battery pack, and vehicle

CN123018373APending Publication Date: 2026-10-30BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610056127.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本申请旨在提供一种电池、电池包及车辆,用于解决电池中绝缘膜难以抑制热失控,导致壳体大面热熔破孔以及绝缘膜机械强度薄弱问题,从而提升电池安全性能

Benefits of technology

在本申请的实施例中,电池包括裸电芯、绝缘膜和壳体,裸电芯封装于壳体内,绝缘膜包覆裸电芯且位于裸电芯和壳体之间;绝缘膜包括膜体和涂层,涂层位于膜体表面且朝向壳体;涂层包括热膨胀微球。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018373A_ABST
    Figure CN123018373A_ABST
Patent Text Reader

Abstract

The application discloses a battery, a battery pack and a vehicle. The battery comprises a bare cell, an insulating film and a shell. The bare cell is packaged in the shell, and the insulating film is wrapped around the bare cell and located between the bare cell and the shell. The insulating film comprises a film body and a coating layer. The coating layer is located on the surface of the film body and faces the shell. The coating layer comprises thermal expansion microspheres. By arranging the coating layer on the surface of the film body of the insulating film and making the coating layer face the shell, the coating layer comprises thermal expansion microspheres. When heated, the thermal expansion microspheres expand until the inflation type sealed cavities are completely formed. Therefore, the insulating film can effectively block heat transfer, so as to achieve the heat insulation effect, reduce the large surface temperature of the bare cell, improve the large surface thermal melting hole problem, and thus improve the safety performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of new energy technology, specifically relating to a battery, a battery pack, and a vehicle. Background Technology

[0002] With the rapid development of new energy vehicles, energy storage power stations, and portable electronic devices, batteries, as their core power source, are becoming increasingly important. Batteries are typically composed of auxiliary components, including positive electrode, negative electrode, separator, electrolyte, insulating film, and casing. Their overall performance and safety directly affect the reliability of end products and user experience.

[0003] As a critical safety component, the insulating film provides insulation and thermal insulation. However, in related technologies, when a battery experiences thermal runaway, the insulating film struggles to suppress its propagation, easily leading to excessively high local temperatures in the casing, causing it to melt and break down, resulting in serious safety accidents. Furthermore, due to its weak mechanical strength, the insulating film is prone to wrinkles, cracks, and peeling under the cyclic stress of battery assembly and long-term charge-discharge cycles. This not only directly damages its insulation and thermal insulation functions but may also induce short circuits in the battery's internal electrode plates due to debris or burrs generated from film damage, further exacerbating battery safety hazards. Summary of the Invention

[0004] This application aims to provide a battery, battery pack, and vehicle to solve the problems of the insulation film in the battery being unable to suppress thermal runaway, resulting in large-area thermal melting and rupture of the casing and weak mechanical strength of the insulation film, thereby improving the battery safety performance.

[0005] To solve the above-mentioned technical problems, this application is implemented as follows: In a first aspect, embodiments of this application provide a battery including a bare cell, an insulating film, and a casing, wherein the bare cell is encapsulated within the casing, and the insulating film covers the bare cell and is located between the bare cell and the casing; The insulating film includes a film body and a coating, wherein the coating is located on the surface of the film body and faces the housing; The coating comprises thermally expandable microspheres.

[0006] Optionally, the thermally expandable microspheres include a core and a coating layer disposed on the surface of the core, wherein the core comprises an alkane, and the coating layer comprises a polymer with a molecular weight of 10. 4 ~10 6 .

[0007] Optionally, the thickness of the coating is 20 to 100 micrometers.

[0008] Optionally, the coating further includes a binder, wherein, by mass fraction, the amount of thermally expandable microspheres added in the coating is 75% to 95%, and the amount of binder added is 5% to 25%.

[0009] Optionally, the density of the thermally expandable microspheres before thermal expansion is 400~1200 kg / m³. 3 The density of the thermally expandable microspheres after thermal expansion is 20~30 kg / m³. 3 ; and / or, The diameter of the thermally expandable microspheres before thermal expansion is 10-50 micrometers, and the diameter of the thermally expandable microspheres after thermal expansion is 30-200 micrometers.

[0010] Optionally, the adhesive includes one or more of vinylidene chloride-hexafluoropropylene copolymer, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid.

[0011] Optionally, the polymer comprises one or more of polyvinyl alcohol, polystyrene, and polyacrylate; and / or, The alkanes include one or more of methane, ethane, propane, n-butane, isobutane, n-pentane, n-hexane, n-heptane, n-tridecane, and n-hexadecane.

[0012] Optionally, the amount of thermally expandable microspheres added is 82% to 95%, and the amount of binder added is 5% to 18%.

[0013] Secondly, embodiments of this application propose a battery pack including the battery described above.

[0014] Thirdly, embodiments of this application propose a vehicle including the aforementioned battery pack, wherein the battery pack serves as a power supply for the vehicle.

[0015] Compared with the prior art, this application has at least the following advantages: In embodiments of this application, the battery includes a bare cell, an insulating film, and a casing. The bare cell is encapsulated within the casing, and the insulating film covers the bare cell and is located between the bare cell and the casing. The insulating film includes a film body and a coating. The coating is located on the surface of the film body and faces the casing. The coating includes thermally expandable microspheres.

[0016] By setting a coating on the surface of the insulating film with the coating facing the shell, the coating includes thermally expandable microspheres. When heated, the thermally expandable microspheres expand until they fully expand to form an inflatable sealed cavity. The expanded microspheres can form a porous structure, thereby giving the insulating film good insulation and heat insulation performance. It can effectively block heat transfer, thereby achieving a heat insulation effect, reducing the temperature of the bare cell surface, and improving the problem of large-area thermal melting and puncture.

[0017] Meanwhile, the thermal expansion microspheres have an elastic buffer function. When heated and expanded, the thermal expansion microspheres form an emergency reinforced heat insulation layer, which effectively relieves cyclic stress and thermal stress, significantly improves the mechanical strength of the insulating film, solves the problem of weak strength of traditional insulating films, and thus improves the safety performance of the battery.

[0018] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0019] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 This paper shows a schematic diagram of the battery structure before thermal expansion according to an embodiment of this application; Figure 2 A schematic diagram of the battery structure after thermal expansion according to an embodiment of this application is shown; Figure 3 A schematic diagram of the structure of the thermally expanded microspheres according to an embodiment of this application is shown; Figure 4 This paper shows a volume comparison diagram of the thermally expandable microspheres before and after thermal expansion according to an embodiment of this application. Figure 4 Diagram A shows the volume of the thermally expanding microspheres before thermal expansion. Figure 4 Figure B shows the volume of the thermally expanded microspheres after thermal expansion. Figure 5 This paper shows a large-area shell state diagram during battery thermal runaway in Embodiment 1 of this application; Figure 6 This paper shows a large-area shell state diagram during battery thermal runaway in Embodiment 2 of this application; Figure 7 This paper shows a large-area shell state diagram during battery thermal runaway in Embodiment 3 of this application; Figure 8 This paper shows a large-area shell state diagram during battery thermal runaway in Embodiment 4 of this application; Figure 9 This paper shows a large-area shell state diagram during battery thermal runaway in Embodiment 5 of this application; Figure 10 This paper shows a large-area shell state diagram during battery thermal runaway in Embodiment 6 of this application; Figure 11 This paper shows a large-area shell state diagram during battery thermal runaway in Embodiment 7 of this application; Figure 12 This paper shows a large-area shell state diagram during battery thermal runaway in Embodiment 8 of this application; Figure 13 The diagram shows the state of the outer casing during thermal runaway of the battery in Comparative Example 1 of this application.

[0020] Figure label: 1-Battery, 11-Bare cell, 12-Casing, 13-Insulating film, 131-Film body, 132-Coating, 1321-Core, 1322-Covering layer. Detailed Implementation

[0021] The embodiments of this application will now be described in detail. Examples of these embodiments are illustrated in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.

[0022] With the rapid development of new energy vehicles, energy storage power stations, and portable electronic devices, secondary batteries, as their core power source, are becoming increasingly important. Among them, lithium batteries, with their advantages of high energy density and long cycle life, have become the most widely used battery system. Lithium batteries are typically composed of auxiliary components including a positive electrode, negative electrode, separator, electrolyte, insulating film, and casing. Their comprehensive performance and safety directly affect the reliability of end products and user experience.

[0023] In the complex structure of lithium batteries, the insulating film (usually Mylar film, i.e., polyester film) is a critical safety component. It is primarily wrapped around the bare cell, and its core function is to provide reliable insulation between the bare cell and the metal casing, effectively preventing internal short circuits caused by contact. Simultaneously, this insulating film also forms a physical barrier, preventing leakage of electrolytes and other substances inside the battery to a certain extent, thus playing a positive role in improving the overall safety and environmental friendliness of the battery.

[0024] However, the traditional insulation solutions represented by Mylar films primarily focus on insulation and leak prevention, with generally poor thermal insulation performance. When a battery experiences thermal runaway, this insulating film cannot effectively block heat transfer between cells or between the cell and the casing, making it difficult to suppress the spread of thermal runaway. This can easily lead to localized overheating of the casing, causing it to melt and break down, resulting in serious safety accidents. To compensate for this deficiency, existing technologies have developed optimized solutions by adding millimeter-thick heat insulation plates to the Mylar film (e.g., the structure disclosed in patent CN221379651U). However, in such solutions, the thicker heat insulation plates significantly increase the overall thickness of the cell module, occupying a large portion of the limited internal space of the battery, resulting in higher energy density loss. Furthermore, due to structural limitations, the heat insulation plates often cannot achieve 100% seamless coverage of the entire bare cell surface, leaving blind spots and failing to provide comprehensive and effective protection.

[0025] Therefore, developing a new solution that combines lightweight design, high-performance thermal insulation, and more comprehensive protection has become a pressing technical problem to be solved in this field.

[0026] This application aims to solve the problems of the difficulty in suppressing thermal runaway in the insulating film of batteries, resulting in large-area thermal melting and rupture of the casing and weak mechanical strength of the insulating film. In a first aspect, embodiments of this application provide a battery 1, such as… Figure 1-3 As shown, it includes a bare battery cell 11, a housing 12 and an insulating film 13. The bare battery cell 11 is encapsulated in the housing 12, and the insulating film 13 covers the bare battery cell 11 and is located between the bare battery cell 11 and the housing 12. The insulating film 13 includes a film body 131 and a coating 132, the coating 132 being located on the surface of the film body 131 and facing the housing 12; Coating 132 includes thermally expandable microspheres.

[0027] It should be noted that the insulating film 13 includes a film body 131, which can be a Mylar film, i.e., biaxially oriented polyester film (BoPET). The thickness of the film body 131 ranges from 50 to 150 micrometers. For example, the thickness range can be one or any two of the following: 50 micrometers, 60 micrometers, 70 micrometers, 80 micrometers, 90 micrometers, 100 micrometers, 120 micrometers, and 150 micrometers. In the embodiments of this application, a Mylar film thickness of 100 micrometers is preferably selected.

[0028] In this embodiment, a coating is formed on the surface of the insulating film, facing the casing. The coating includes thermally expandable microspheres. When heated, the microspheres expand until they fully expand to form an inflatable, sealed cavity. The expanded microspheres form a porous structure, thus giving the insulating film excellent insulation and heat insulation properties. This effectively blocks heat transfer, achieving a heat insulation effect, reducing the surface temperature of the bare cell, and improving the problem of large-area thermal melting and puncture. Simultaneously, the thermally expandable microspheres have an elastic buffering function. When heated and expanding, they form an emergency reinforced heat insulation layer, effectively alleviating cyclic stress and thermal stress, significantly improving the mechanical strength of the insulating film, solving the problem of weak strength in traditional insulating films, and thus improving the battery's safety performance.

[0029] Optionally, in one embodiment, the thermally expandable microsphere includes a core 1321 and a coating layer 1322 disposed on the surface of the core. The core includes an alkane, and the coating layer includes a polymer with a molecular weight of 10. 4 ~10 6 .

[0030] The specific principle behind the expansion of thermally expandable microspheres at room temperature and upon heating is as follows: First stage: When the thermally expanded microspheres are in a normal temperature environment, the alkanes in the core exist in a liquid or low-volatility liquid state, while the polymer of the coating layer is in a glassy state with tightly arranged molecular chains and strong rigidity, which can firmly constrain the alkanes in the core and prevent them from leaking or volatilizing.

[0031] The second stage: When the external temperature rises above the glass transition temperature of the coating polymer, the coating begins to change from a glassy state to a highly elastic state. The thermal motion of the polymer chain segments intensifies, the intermolecular forces weaken, and the coating gradually softens and acquires a certain degree of extensibility. At the same time, heat is transferred to the core through the softened coating. The liquid alkanes begin to absorb heat, rapidly breaking the gas-liquid equilibrium and transforming into a large amount of gaseous alkanes. As the alkane molecules change from a compact liquid state to a loose gaseous state, their volume increases dramatically (the volume can expand by tens of times), causing the pressure inside the core to rise sharply in a short period of time, accumulating energy for subsequent expansion.

[0032] The third stage: As the coating layer stretches, its molecular chains are gradually elongated, and the elastic tension between molecules also increases. When the elastic tension of the coating layer reaches equilibrium with the internal pressure of the gaseous alkanes in the core, the microsphere stops expanding. If the temperature does not rise further at this time, the microsphere can maintain its expanded shape (because the coating layer is still in a highly elastic state and will not shrink immediately).

[0033] Fourth stage: When the external temperature stabilizes within the expansion temperature range or begins to cool slowly, the expanded microspheres enter the morphology stabilization stage. The coating layer changes from a highly elastic state back to a glassy state, the molecular chain movement is restricted, rigidity is restored, and the stretched coating layer structure is frozen. Even if the internal pressure of the gaseous alkanes in the core decreases slightly due to the temperature drop, the coating layer cannot shrink back to its initial form, thus achieving permanent morphology stabilization and forming a stable hollow microsphere structure.

[0034] In this embodiment, a coating is formed on the surface of the insulating film, with the coating facing the shell. The coating includes thermally expandable microspheres. When heated, the alkane core of the thermally expandable microspheres vaporizes, providing the driving force. The thermoplastic, elastic, and airtight coating layer softens accordingly, and the thermally expandable microspheres expand until they fully expand to form an inflatable sealed cavity. The expanded microspheres can form a porous structure, thereby giving the insulating film good insulation and heat insulation properties. It can effectively block heat transfer, thereby achieving a heat insulation effect, reducing the temperature of the bare cell surface, improving the problem of large-area thermal melting and puncture, and thus improving the safety performance of the battery.

[0035] Alternatively, in one embodiment, the coating thickness is 20 to 100 micrometers.

[0036] It should be noted that the coating thickness is 20 to 100 micrometers. For example, the coating thickness can be one or any two of the following values: 20 micrometers, 30 micrometers, 40 micrometers, 50 micrometers, 60 micrometers, 70 micrometers, 80 micrometers, 90 micrometers, and 100 micrometers.

[0037] In this embodiment, the thickness of the coating (20~100 micrometers) is only 1 / 10 to 1 / 50 of that of a traditional heat insulation plate (1-5 mm), which hardly occupies any additional space inside the battery. It can retain the design capacity of the battery electrode assembly to the maximum extent and significantly reduce energy density loss. It is especially suitable for scenarios with stringent requirements for small size and high capacity, such as consumer electronics and power batteries.

[0038] Meanwhile, the micron-level coating has excellent extensibility and adhesion, which can uniformly cover the surface and details of the bare cell, forming a protective layer without dead angles. This avoids the problem of thermal runaway propagation caused by local non-coverage in traditional solutions, and improves the overall safety of the battery.

[0039] Furthermore, the micron-scale coating is thin and has low thermal resistance at room temperature, so it does not affect the battery's daily heat dissipation efficiency; however, when the battery experiences thermal runaway, such as Figure 4 As shown, the thermally expandable microspheres in the coating can rapidly expand when heated (increasing in volume to 10-50 times their initial size), forming a dense hollow heat insulation layer that temporarily blocks heat transfer to the shell. This not only avoids obstruction of conventional heat dissipation but also provides heat insulation protection in emergencies, thus meeting both daily heat dissipation and emergency heat insulation needs.

[0040] Optionally, in one embodiment, the coating further includes a binder, wherein the amount of thermally expandable microspheres added in the coating is 75% to 95% by mass fraction, and the amount of binder added is 5% to 25%.

[0041] It should be noted that the addition amount of thermally expandable microspheres is 75% to 95%. For example, the addition amount of thermally expandable microspheres can be one or any two of the following: 75%, 77%, 79%, 80%, 82%, 85%, 88%, 90%, 92%, 93%, and 95%. A high addition amount of 75% to 95% ensures that the microspheres are evenly distributed and have a sufficiently high density in the coating. After expansion, the microspheres can compress and splice together to form a continuous thermal insulation barrier without obvious gaps, avoiding the formation of holes in the insulation layer due to insufficient microsphere quantity, thus preventing a loss of heat-blocking ability. If the addition amount is less than 75%, the microspheres will not easily form a continuous structure after expansion, and gaps will easily appear in the insulation layer. Heat will quickly penetrate through these gaps, failing to achieve the desired emergency thermal insulation effect.

[0042] It should be noted that the amount of binder added is 5% to 25%. For example, the amount of binder added is one or any two of the following: 5%, 8%, 10%, 12%, 14%, 15%, 18%, 20%, 22%, and 25%. During battery assembly (such as wrapping bare cells and inserting them into the casing), the coating needs to withstand a certain amount of mechanical friction and compression. The amount of binder added is 5% to 25%, which can form physical adsorption or chemical bonding with the surface of the membrane through its own adhesion, anchoring the thermally expanded microspheres to the surface of the membrane and preventing the coating from peeling off or shedding powder in subsequent processes. The minimum addition amount of 5% is the critical value to ensure the bonding strength. If it is less than 5%, the binder cannot completely wrap the surface of the microspheres, and the coating is easy to fall off under slight external force. The upper limit of 25% is to avoid the excessive amount of binder from increasing the rigidity of the coating and affecting the flexibility of the membrane.

[0043] In practice, 5% to 25% by weight of the adhesive is completely dissolved in a mixed solvent of N-methylpyrrolidone and acetone to form a glue solution, with the ratio of the mixed solvent to the adhesive being 5:1 to 10:1. Then, 75% to 95% of the thermally expandable microsphere powder is added to the glue solution and mixed thoroughly to obtain a coating slurry. Finally, the obtained coating slurry is applied to the membrane (Mylar membrane) near the bare cell surface, with a coating thickness of 20 to 100 micrometers, to obtain the insulating film.

[0044] In this embodiment, the high addition amount (75%~95%) of thermally expandable microspheres is functionally focused, ensuring the coating achieves the core objective of emergency thermal insulation; the low addition amount (5%~25%) of binder is structurally supported, ensuring the coating's process feasibility and operational stability without interfering with the core function. The ratio of these two components must be strictly controlled to achieve a balance between function and structure, ensuring thermal insulation performance and thus improving battery safety.

[0045] Optionally, in one embodiment, the density of the thermally expandable microspheres before thermal expansion is 400~1200 kg / m³. 3 The density of the thermally expandable microspheres after thermal expansion is 20~30 kg / m³. 3 .

[0046] It should be noted that the density of the thermally expandable microspheres before thermal expansion is 400~1200 kg / m³. 3 For example, the density before thermal expansion can be 400 kg / m³. 3 500 kg / m 3 600 kg / m 3 700 kg / m 3 800 kg / m 3 900 kg / m 3 1000 kg / m 31100 kg / m 3 1200kg / m 3 The range of one or both of these values. 400~1200 kg / m³ at room temperature. 3 The higher density corresponds to the microspheres being dense solid or semi-solid spheres (with a tightly packed liquid alkane core), which are small in size and compact in structure, and can be uniformly dispersed in micron-scale coatings.

[0047] It should be noted that the density of the thermally expanding microspheres after thermal expansion is 20~30 kg / m³. 3 For example, the density after thermal expansion is 20 kg / m³. 3 21 kg / m 3 22 kg / m 3 23 kg / m 3 24 kg / m 3 25 kg / m 3 28 kg / m 3 30kg / m 3 The value is within the range of one or both of these. The density drops sharply to 20-30 kg / m³ after heating. 3 This means that the microspheres expand to 10 to 50 times their initial size, and the originally dense spheres are transformed into a hollow porous structure (the coating layer is stretched to form a porous shell, and the interior is filled with gaseous alkanes).

[0048] In this embodiment, the density change of the thermally expanded microspheres is essentially the result of the vaporization of the liquid alkane core, leading to volume expansion and overall loosening of the microspheres. The density change of the thermally expanded microspheres before and after heating is 400~1200 kg / m³. 3 Up to 20~30kg / m 3 This is the core physical basis for realizing the transformation from a coating functional body to a high-efficiency thermal barrier. Through the volume expansion caused by the reduction in density and the lightweight porous structure, it not only solves the contradiction between the thinness of the micron-level coating and strong thermal insulation, but also avoids the defects of traditional protective structures that occupy space and are heavy. Ultimately, it provides an efficient, lightweight and space-saving solution for battery thermal runaway protection.

[0049] Optionally, in one embodiment, the diameter of the thermally expandable microspheres before thermal expansion is 10-50 micrometers, and the diameter of the thermally expandable microspheres after thermal expansion is 30-200 micrometers.

[0050] It should be noted that the diameter of the thermally expandable microspheres before thermal expansion is 10-50 micrometers. For example, the diameter before thermal expansion is one or any two of the following values: 10 micrometers, 15 micrometers, 20 micrometers, 25 micrometers, 30 micrometers, 35 micrometers, 40 micrometers, 45 micrometers, and 50 micrometers. At room temperature, microspheres of 10-50 micrometers can be uniformly dispersed in a micrometer-scale coating. The microsphere coating can closely adhere to the curved surfaces and corners of the bare cell (such as the end face of the wound electrode assembly and the root of the electrode tab), and even penetrate into tiny gaps, achieving complete coverage without occupying additional battery space.

[0051] It should be noted that the diameter of the thermally expanded microspheres after thermal expansion is 30-200 micrometers. For example, the diameter after thermal expansion is within the range of one or both of the following: 30 micrometers, 40 micrometers, 50 micrometers, 60 micrometers, 70 micrometers, 80 micrometers, 90 micrometers, 100 micrometers, 120 micrometers, 150 micrometers, 180 micrometers, and 200 micrometers. When the battery experiences thermal runaway, the diameter of the microspheres rapidly increases to 30-200 micrometers. A large number of expanded microspheres compress and stack against each other inside the coating, thickening the original thin coating to hundreds of micrometers, forming a three-dimensional porous thermal insulation layer. The expanded microspheres can fill the gaps inside the battery as needed, depending on the size of the gaps. If the gaps are small (e.g., 100 micrometers), the microspheres can be expanded to 100-150 micrometers to fill the gaps. If the gaps are large (e.g., 300 micrometers), the microspheres can be fully expanded to 200 micrometers. Together with the stacking of adjacent microspheres, they form a complete heat insulation layer, avoiding the problem of heat penetrating through the gaps. This truly achieves all-round heat insulation protection between the bare cell and the casing.

[0052] In this embodiment, the diameter change of the thermally expanding microspheres before and after heating (from 10-50 micrometers to 30-200 micrometers) is key to achieving spatial adaptation, three-dimensional thermal insulation, and comprehensive protection within a micrometer-scale coating. The 10-50 micrometer range adapts to thin coatings and complex contours, while the 30-200 micrometer range constructs an effective thermal barrier. The controllable expansion ratio ensures reliable protection, ultimately addressing the shortcomings of traditional protection solutions such as space occupation, blind spots, and susceptibility to failure, thereby improving battery safety performance.

[0053] Optionally, in one embodiment, the adhesive includes one or more of vinylidene chloride-hexafluoropropylene copolymer, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid.

[0054] It should be noted that the preferred adhesives in this application are vinylidene chloride-hexafluoropropylene copolymer and polyvinylidene fluoride.

[0055] Specifically, the vinylidene chloride-hexafluoropropylene copolymer contains fluorine atoms (hexafluoropropylene units) and chlorine atoms (vinylidene chloride units) in its molecular chain. The strong electronegativity of fluorine and chlorine atoms makes the molecular chain highly polar and chemically inert, which can resist the corrosion of carbonate solvents and lithium salts (such as LiPF6) in the electrolyte, prevent the binder from being dissolved or swollen by the electrolyte, and ensure that the coating does not fall off for a long time and the microspheres do not agglomerate. At the same time, the copolymer has good sealing properties after film formation, and can form a dense coating layer on the surface of the microspheres. At room temperature, it can prevent the trace volatilization of alkanes in the core of the thermally expanding microspheres, ensure the stability of the expansion performance of the microspheres, and avoid the decrease in expansion ratio due to alkane leakage.

[0056] Polyvinylidene fluoride (PVDF) has high molecular chain regularity and excellent mechanical strength after film formation. It can firmly anchor thermally expanding microspheres to the film (such as Mylar film). During battery assembly (such as bare cell insertion, winding / stacking), the coating needs to withstand mechanical forces such as compression and friction. PVDF can prevent microspheres from falling off or the coating from cracking. At the same time, PVDF has a wide range of high and low temperature resistance. When the battery is charged and discharged at low temperature (such as -20℃) or cycled at normal temperature (25℃~60℃), the structure is stable and will not become embrittled (low temperature) or softened (high temperature) due to temperature fluctuations. This ensures that the coating is always tightly attached to the film and does not affect the dispersibility of microspheres. In addition, PVDF has strong interfacial adhesion to the film and can form a strong bond through intermolecular forces, which further improves the structural stability of the coating.

[0057] Alternatively, in one embodiment, the binder includes carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), which are used in combination to provide high flexibility and low interfacial resistance, adapting to the complex shape of bare cells.

[0058] Polyacrylic acid (PAA) has high adhesion and pH responsiveness, making it suitable for dense coating of microspheres.

[0059] In the embodiments of this application, the above-mentioned adhesive can be matched to the battery operating conditions as needed, and is resistant to electrolyte corrosion (vinylidene chloride-hexafluoropropylene copolymer, PVDF), mechanical stress (PVDF), and can be applied to complex shapes (CMC+SBR). It can also enhance adhesion and environmental protection processes (PAA). Whether used alone or in combination, it can ensure that the coating is firmly adhered, durable, and highly adaptable, providing stable structural support for the thermal expansion microspheres to play an emergency heat insulation role.

[0060] Optionally, in one embodiment, the polymer includes one or more of polyvinyl alcohol, polystyrene, and polyacrylate.

[0061] It should be noted that polyvinyl alcohol (PVA) contains a large number of hydroxyl groups (-OH) in its molecular chain. Hydrogen bonds can be formed between the hydroxyl groups, making the coating layer structure dense and highly sealing, which can effectively block the trace volatilization of liquid alkanes. At the same time, PVA has good hydrophilicity. If the microspheres are used in an aqueous coating system (such as with CMC binder), the hydroxyl groups on their surface can form hydrogen bonds with the aqueous binder, improving the dispersibility of the microspheres in the coating and preventing agglomeration.

[0062] Polystyrene (PS) has a non-polar molecular chain structure, resulting in high density and a smooth surface after film formation. It has good compatibility with non-polar alkane cores (no swelling effect) and can form a stable sealing barrier. Furthermore, PS has a relatively high glass transition temperature (Tg of 100~110℃), and the coating layer is rigid at room temperature, which can withstand certain external pressures (such as the compression during battery assembly) and prevent the core alkane from leaking due to shell pressure.

[0063] Polyacrylate (PA) has polar ester groups (-COOR) on the side of its molecular chain. After film formation, it has excellent airtightness and better barrier efficiency against alkanes than most general polymers. At the same time, the Tg of PA can be controlled by adjusting the length of the ester alkyl chain, and the softening temperature of the coating layer can be precisely designed according to the thermal runaway temperature of the battery to ensure thermal expansion and room temperature sealing.

[0064] All three polymers mentioned above are thermoplastic polymers. When heated above their glass transition temperature (Tg), the thermal motion of the molecular chain segments intensifies, and the coating layer transitions from a glassy state to a highly elastic state (softening but not melting). At this point, the coating layer no longer rigidly constrains the core and can be passively stretched by the internal pressure generated by alkane vaporization, providing deformable space for the expansion of the microspheres. Furthermore, these three polymers exhibit good compatibility with commonly used battery binders (such as PVDF, CMC, and PAA).

[0065] In this embodiment, polyvinyl alcohol, polystyrene, and polyacrylate are used as the coating polymers of the thermally expandable microspheres. They are the core carriers for the microspheres to achieve sealing, expansion, shaping, and adaptation functions. Their structural characteristics determine the expansion temperature, expansion ratio, stability, and compatibility of the microspheres, ultimately ensuring that the microspheres can stably form a high-efficiency heat insulation layer and play an emergency protection role when the battery experiences thermal runaway.

[0066] Optionally, in one embodiment, the alkane includes one or more of methane, ethane, propane, n-butane, isobutane, n-pentane, n-hexane, n-heptane, n-tridecane, and n-hexadecane.

[0067] It should be noted that low-carbon alkanes (C1-C7, such as methane, propane, and isobutane) are suitable for medium- and low-temperature thermal runaway scenarios (e.g., 100~200℃).

[0068] Medium-carbon alkanes (C13, C16, such as n-tetane and n-hexadecane) are suitable for high-temperature thermal runaway scenarios (e.g., 200~300℃).

[0069] In practical applications, 2 to 3 alkanes with different carbon numbers are often combined (such as isobutane and n-pentane, n-hexane and n-tetane). The core is to solve the problem of narrow temperature response range of single alkanes and adapt to the complex temperature changes of battery thermal runaway.

[0070] In this embodiment, the alkane is the core of thermal expansion microspheres. Its boiling point and vapor pressure characteristics determine the expansion trigger temperature and expansion intensity of the microspheres. Alkanes with different carbon numbers can be used individually or in combination to adapt to different thermal runaway scenarios of batteries. Alkanes are not only the power source for expansion, but their gaseous form can also enhance the heat insulation effect of the microspheres and ensure the stability of the microspheres' performance throughout the battery's life cycle. Ultimately, this ensures that the microspheres can expand stably when needed, forming a highly efficient hollow heat insulation layer and improving the safety performance of the battery.

[0071] Optionally, in one embodiment, the amount of thermally expandable microspheres added is 82% to 95%, and the amount of binder added is 5% to 18%.

[0072] It should be noted that the addition amount of thermally expandable microspheres is 82% to 95%. For example, the addition amount of thermally expandable microspheres is one or any two of the following: 82%, 84%, 85%, 86%, 88%, 90%, 91%, 93%, and 95%. An addition amount of 82% to 95% allows the microspheres to be evenly and densely distributed in the coating. When heated and expanded (the diameter of the microspheres increases from 10-50 micrometers to 30-200 micrometers), a large number of expanded microspheres will squeeze and splice together, filling the internal space of the coating and forming a hollow porous heat insulation layer without obvious gaps.

[0073] It should be noted that the amount of binder added is 5% to 18%. For example, the amount of binder added is one or any two of the following: 5%, 8%, 10%, 12%, 15%, and 18%. The binder is the structural adhesive of the coating. The addition amount of 5% to 18% ensures that the coating can adhere firmly to the film and maintain its morphological integrity without diluting the microspheres or affecting the expansion.

[0074] In this embodiment, the amount of thermally expandable microspheres added is 82% to 95%, and the amount of binder added is 5% to 18%. Only within the above range can a balance be achieved between maximizing thermal insulation performance and meeting structural stability standards, thereby improving the safety performance of the battery.

[0075] Secondly, embodiments of this application provide a battery pack including the battery described above.

[0076] Thirdly, embodiments of this application provide a vehicle including the aforementioned battery pack, which serves as the vehicle's power supply.

[0077] The above-described battery pack embodiment includes the aforementioned battery and achieves the same technical effect. To avoid repetition, it will not be described again here. For relevant details, please refer to the description of the battery embodiment.

[0078] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.

[0079] The present application will be described in detail below through embodiments.

[0080] Test method: Heating boundary test: The battery system consists of a square aluminum 6-series casing and graphite, with dimensions of 52*148*106mm. The test voltage is 2.8V~4.4V, the thermal expansion start temperature is 110℃~220℃, and the heating rate is 5℃ / min. The temperature of the large surface area and the state of the large surface casing are recorded during thermal runaway.

[0081] Example 1 (1) Preparation of thermally expandable microspheres Thermally expandable microspheres were obtained by using n-butane as the core and polyvinyl alcohol (molecular weight 5-15W) as the coating layer.

[0082] (2) Preparation of coating slurry 50g (25%) of vinylidene chloride-hexafluoropropylene copolymer was used as a binder and completely dissolved in 200mL of a mixed solvent of N-methylpyrrolidone and acetone to form a glue solution. 150g (75%) of thermally expandable microsphere powder was added to the glue solution and mixed thoroughly to obtain a coating slurry.

[0083] (3) Preparation of insulating film The above-mentioned coating slurry is uniformly applied to the surface of the membrane (Mylar membrane). The Mylar membrane has a thickness of 100 micrometers, and the coating thickness is 20~100 micrometers. After drying, an insulating film is obtained.

[0084] (4) Battery preparation The bare battery cell, insulating film, and square aluminum shell are packaged together. The bare battery cell is encapsulated inside the shell, and the insulating film covers the bare battery cell and is located between the bare battery cell and the square aluminum shell. The insulating film faces the shell to obtain the battery.

[0085] Example 2 The difference between Example 2 and Example 1 is as follows: In Example 2, the amounts of thermally expanded microspheres and binder in the preparation of the coating slurry in step (2) were adjusted to 85% and 15%, respectively.

[0086] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0087] Example 3 The difference between Example 3 and Example 1 is as follows: Example 3 changed the polymer in the preparation of thermally expanded microspheres in step (1) to polyvinyl alcohol and polystyrene.

[0088] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0089] Example 4 The difference between Example 4 and Example 1 is as follows: In Example 4, the alkane in the preparation of thermally expanded microspheres in step (1) was changed to n-tetane.

[0090] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0091] Example 5 The difference between Example 5 and Example 1 is as follows: Example 5: The binder in the preparation of the coating slurry in step (2) was changed to polyvinylidene fluoride.

[0092] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0093] Example 6 The difference between Example 6 and Example 1 is: In Example 6, the amounts of thermally expanded microspheres and binder in the preparation of the coating slurry in step (2) were adjusted to 95% and 5%, respectively.

[0094] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0095] Example 7 The difference between Example 7 and Example 1 is as follows: In Example 7, the amounts of thermally expanded microspheres and binder in the preparation of the coating slurry in step (2) were adjusted to 90% and 10%, respectively.

[0096] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0097] Example 8 The difference between Example 8 and Example 1 is: In Example 8, the amounts of thermally expanded microspheres and binder in the preparation of the coating slurry in step (2) were adjusted to 82% and 18%, respectively.

[0098] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0099] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: Comparative Example 1: No thermal expansion microspheres, binders, or coatings were added.

[0100] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.

[0101] The batteries obtained in each embodiment and comparative example were subjected to heating boundary tests, and the results are shown in Table 1. In each embodiment, the density of the thermally expanding microspheres before thermal expansion was 400~1200 kg / m³. 3 Within this range, the density of the thermally expanding microspheres after thermal expansion is 20~30 kg / m³. 3 Within this range, the diameter of the thermally expandable microspheres before thermal expansion is 10-50 micrometers, and the diameter of the thermally expandable microspheres after thermal expansion is 30-200 micrometers.

[0102] Table 1

[0103] As shown in Table 1, the batteries in the comparative example, without a coating, exhibited a high surface temperature (621°C) during thermal runaway, with severe surface damage. In the embodiments, with a coating on the insulating film surface, the surface temperature during thermal runaway was generally 70-150°C lower than in the comparative example, the surface remained intact, and the coating thickness was 20-100 micrometers. Therefore, this application's coating on the insulating film surface effectively blocks heat transfer, achieving a heat insulation effect, reducing the surface temperature of the bare cell, improving the problem of surface thermal melting and puncture, and thus enhancing battery safety. The coating thickness is in the micrometer range, occupying almost no additional internal battery space, maximizing the preservation of the battery electrode design capacity, and significantly reducing energy density loss.

[0104] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0105] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.

Claims

1. A battery, characterized in that, The device includes a bare battery cell, an insulating film, and a housing. The bare battery cell is encapsulated within the housing, and the insulating film covers the bare battery cell and is located between the bare battery cell and the housing. The insulating film includes a film body and a coating, wherein the coating is located on the surface of the film body and faces the housing; The coating comprises thermally expandable microspheres.

2. The battery according to claim 1, characterized in that, The thermally expandable microspheres include a core and a coating layer disposed on the surface of the core. The core includes an alkane, and the coating layer includes a polymer with a molecular weight of 10. 4 ~10 6 .

3. The battery according to any one of claims 1-2, characterized in that, The coating thickness is 20-100 micrometers.

4. The battery according to claim 1, characterized in that, The coating also includes a binder. By mass fraction, the amount of thermally expandable microspheres added in the coating is 75% to 95%, and the amount of binder added is 5% to 25%.

5. The battery according to claim 1, characterized in that, The density of the thermally expandable microspheres before thermal expansion is 400~1200 kg / m³. 3 The density of the thermally expandable microspheres after thermal expansion is 20~30 kg / m³. 3 ; and / or, The diameter of the thermally expandable microspheres before thermal expansion is 10-50 micrometers, and the diameter of the thermally expandable microspheres after thermal expansion is 30-200 micrometers.

6. The battery according to claim 4, characterized in that, The adhesive includes one or more of vinylidene chloride-hexafluoropropylene copolymer, polyvinylidene fluoride, carboxymethyl cellulose, styrene-butadiene rubber, and polyacrylic acid.

7. The battery according to claim 2, characterized in that, The polymer includes one or more of polyvinyl alcohol, polystyrene, and polyacrylate; and / or, The alkanes include one or more of methane, ethane, propane, n-butane, isobutane, n-pentane, n-hexane, n-heptane, n-tridecane, and n-hexadecane.

8. The battery according to claim 4, characterized in that, The amount of thermally expandable microspheres added is 82%~95%, and the amount of binder added is 5%~18%.

9. A battery pack, characterized in that, Includes the battery as described in any one of claims 1 to 8.

10. A vehicle, characterized in that, The battery pack includes the battery pack of claim 9, which serves as a power supply for the vehicle.